Interpellation to the Social Sciences: the challenge of understanding contemporary society - Arnold-Cathalifaud, Marcelo (2017)
Latin America needs robust, critical and rigorous social sciences from an institutional approach; it needs disciplines that contribute to the understanding of contemporary society and to meet its urgent social demands. This article presents alternatives to address productively the changing scenarios that characterized the first decades of this century at local, regional and global levels in our researches. First, the exposition analyzes how our disciplines face the demand for knowledge in the current global context; secondly, it emphasizes internal and external obstacles that inhibit their contributions deployment, and finally it presents a programmatic proposal, inspired by the systems and complexity theories emphasizing its relevance for Latin America.